2016
DOI: 10.1515/infl-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Burn the house, save the day: pyroptosis in pathogen restriction

Abstract: Many programmed cell death pathways are essential for organogenesis, development, immunity and the maintenance of homeostasis in multicellular organisms. Pyroptosis, a highly proinflammatory form of cell death, is a critical innate immune response to prevent intracellular infection. Pyroptosis is induced upon the activation of proinflammatory caspases within macromolecular signalling platforms called inflammasomes. This article reviews our understanding of pyroptosis induction, the function of inflammatory cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Inflammasome-mediated activation results in a proinflammatory form of programmed cell death known as pyroptosis ( 7 ). As reviewed by Man and colleagues ( 8 ), pyroptosis is a form of necrotic and inflammatory programmed cell death induced by inflammatory caspases.…”
Section: Ergosterol As An Immunoactive Fungal Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Inflammasome-mediated activation results in a proinflammatory form of programmed cell death known as pyroptosis ( 7 ). As reviewed by Man and colleagues ( 8 ), pyroptosis is a form of necrotic and inflammatory programmed cell death induced by inflammatory caspases.…”
Section: Ergosterol As An Immunoactive Fungal Moleculementioning
confidence: 99%
“…The caspases required for activation of pyroptosis include human and mouse caspase-1, human caspase-4 and caspase-5, and mouse caspase-11 ( 8 ). Caspases mediate cleavage and activation of the pore-forming effector protein gasdermin D. Pore-mediated cell rupture results in the extracellular release of proinflammatory cytokines and alarmins and in danger-associated molecular patterns, which participate in the control of bacterial, viral, fungal, and protozoan infections ( 7 , 8 ). Results obtained from experimental models by the use of mice deficient in caspase-1 and/or caspase-11 and infected with Aspergillus fumigatus , Paracoccidioides brasiliensis , or Candida albicans have suggested that organ damage, increased fungal dissemination, and reduced host survival might be related to pyroptosis ( 9 11 ).…”
Section: Ergosterol As An Immunoactive Fungal Moleculementioning
confidence: 99%
“…ROS production in macrophages is always related to inflammasome activation, which may directly cause cellular damage, oxidative stress, and pyroptotic processes ( Shen et al, 2020 ; Wang et al., 2019b ). Pyroptosis in pathogen restriction is a critical innate immune response to prevent intracellular infection ( Boucher et al., 2015 ). It is emerging as an important mechanism of microbial clearance, during which the activation of caspase-1 leads to the production of IL-1β and IL-18 ( Boucher et al., 2015 ; Xia et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis in pathogen restriction is a critical innate immune response to prevent intracellular infection ( Boucher et al., 2015 ). It is emerging as an important mechanism of microbial clearance, during which the activation of caspase-1 leads to the production of IL-1β and IL-18 ( Boucher et al., 2015 ; Xia et al., 2019 ). In LEW rat macrophages, T. gondii infection could activate the NLRP1 inflammasome, secretion of mature IL-1β, resulting in pyroptosis, and inhibition of parasite replication ( Cavailles et al., 2014 ; Cirelli et al., 2014 ; Ewald et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is inflammatory programmed cell death, mainly mediated by caspase-1, that has emerged as an important mechanism of innate immunity against pathogens (Boucher et al, 2016;Jorgensen and Miao, 2015). The main activation pathway of caspase-1 occurs through inflammasome, a signaling protein complex assembled in response to cell disorders or intracellular pathogens.…”
Section: Introductionmentioning
confidence: 99%